Karakteristik Fisik, Mekanik Dan Zona Hambat Edible Film Dari Pati singkong Karet (Manihot glaziovii) Dengan Penambahan Gliserol Dan Ekstrak Jahe Merah (Zingiber officinale Var Rubrum) Sebagai Penghambat Bakteri Salmonella - Lady Agitasi Amrillah; Warkoyo Warkoyo; Desiana Nuriza Putri (Food Technology and Halal Science Journal, 2019)
The edible film is one of the innovations used to overcome the food packaging problem. Components of edible films are hydrocolloids, lipids, and composites. Glycerol belongs to the hydrocolloid group which serves to maintain the solidity of the film sheet. The edible active film allegedly can inhibit physical, chemicals, and microbiology problems in the packaging which will affect the decline of food quality during storage. With the active compounds contained in red ginger it is expected to inhibit the growth of Salmonella bacteria. The purpose of this study was to determine the effect of the addition of different concentrations of glycerol and red ginger extract on the physical, mechanical, and inhibitory zones in the resulting edible film produced. This research used a nested design with 2 factors. The first factor was the addition of 20% glycerol concentration; 25%; 30% while the second factor is the addition of 0% red ginger extract; 0.5%; 1%; 1.5%. The treatments were 12 treatments with 3 replications. The parameters of this study include thickness, tensile strength, elasticity, WVTR, transparency, moisture content, solubility, density, and edible inhibition zone against Salmonella bacteria. The results showed that edible active red ginger film with the addition of glycerol had a significant effect on thickness, transparency, tensile strength and inhibition zone. On the addition of red ginger extract, 1.5% can inhibit the growth of Salmonella bacteria up to 34.17 mm.